2012
DOI: 10.2166/washdev.2012.078
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of social acceptance and scope of scaling up urine diversion dehydration toilets in Kenya

Abstract: A urine diversion dehydration toilet (UDDT) is a kind of toilet which can be used to recover resources such as nutrients and can also be an option to improve the sanitary situation in low income countries. A structured questionnaire survey, key informant interviews, participatory approaches such as focus group discussion (FGD) and mass gathering were carried out in Kenya to assess social acceptance and scope of scaling up of UDDTs. The results showed that almost all respondents among UDDT users and non-users h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…A similar study conducted in Kenya found that most of the study participants overcame social and cultural barriers through public awareness andacceptance of Eco-san toilets.They were, now, using human urine as fertilizeron their farms. Moreover, they recommended the practice to awider community [30].Likewise, a similar study conducted in Indonesia [31] found that Indonesians accepted Eco-san toilets because of theperceived environmental friendliness and the fertilizer value.Some of the participants thought the possibilitythat the innovationused in the Eco-san system could be ofvalue.They noted the advantage of using the Eco-san toilet and applying urine as fertilizer in school gardens over other types of toilets and chemical fertilizers. They also reported the economicalbene ts the Eco-san toilet can achievein valuing and accepting Eco-san innovations.…”
Section: Discussionmentioning
confidence: 98%
“…A similar study conducted in Kenya found that most of the study participants overcame social and cultural barriers through public awareness andacceptance of Eco-san toilets.They were, now, using human urine as fertilizeron their farms. Moreover, they recommended the practice to awider community [30].Likewise, a similar study conducted in Indonesia [31] found that Indonesians accepted Eco-san toilets because of theperceived environmental friendliness and the fertilizer value.Some of the participants thought the possibilitythat the innovationused in the Eco-san system could be ofvalue.They noted the advantage of using the Eco-san toilet and applying urine as fertilizer in school gardens over other types of toilets and chemical fertilizers. They also reported the economicalbene ts the Eco-san toilet can achievein valuing and accepting Eco-san innovations.…”
Section: Discussionmentioning
confidence: 98%
“…See reference 1, Uddin et al (2012). A number of respondents noted that visitors from more rural areas frequently inquired about how to obtain a CLSS toilet.…”
Section: F I G U R E 8 a Reasons For Using The Clss Toilets F I G U Rmentioning
confidence: 99%
“…Urine diversion requires a specially designed seat-riser or squatting slab or pan that is functionally reliable and socially acceptable. The basic idea of how to avoid mixing urine and feces is simple: the toilet user should sit or squat over some kind of dividing wall so that feces drop behind the wall and urine passes in front of the wall [19,20].…”
Section: Moisture Contentmentioning
confidence: 99%